Electrochemical Study of Ion Transfers Processes at the Interfaces between Water and Trifluorotoluene and Its Derivatives. Issue 13 (9th June 2022) - Liu, Junjie; Zheng, Xinhe; Hua, Yutong; Deng, Jintao; He, Peng; Yu, Zhengyou; Zhang, Xianhao; Shi, Xiaohong; Shao, Yuanhua
Abstract: As one phase constituting of a liquid/liquid (L/L) interface, suitable organic solvents are of great significance for the study of electrochemistry at a L/L interface. In this work, the thermodynamic and kinetic parameters of simple ion transfer (IT) at the water/trifluorotoluene (W/TFT) interface were measured using micro‐ and nanopipettes voltammetry, respectively. In addition to the study of model ions, we have also explored some ions whose transfer potentials are close to the two ends of the potential window. Inspired by the work of the W/TFT interface, we also further developed two novel L/L interfaces and investigated various simple IT reactions based on the W/ o‐ and p ‐methylbenzotrifluoride (W/ o ‐ and p‐ MBTF) interfaces. The transfer potential and Gibbs energy of ITs across the W/ o ‐and p‐ MBTF interface were determined by the analysis of the electrochemical voltametric curves. Special attention should be paid to that we can observe the IT peak or steady‐state of tetraamyl ammonium (TAA + ) at W/ o ‐ and p ‐MBTF interfaces with no difficulty, which is rather challenging at other L/L interfaces. Compared to the classical W/1, 2‐dichloroethane (DCE) and W/nitrobenzene (NB) interfaces, the W/TFT and its derivatives interfaces exhibit low toxicity, favourable stability, and wider potential windows, which can be better choices for replacing the traditional organic solvents in the electrochemical study at a L/L interface. Abstract : Ion transfer at the interfaces : Thermodynamic and kinetic behaviors of simple ion transfers at the water/trifluorotoluene (W/TFT) interface are investigated in this work. Two novel types of liquid/liquid (L/L) interfaces, W/ o ‐ and p ‐methylbenzotrifluoride (W/ o ‐ and p ‐MBTF) interfaces, have also been established and their application in electrochemistry at L/L interfaces are discussed.